A Pediatric Office-Based Quality Improvement Project in a Rural Health Clinic: Retrospective Evaluation - Patricia McNamar; Deborah G Loman (Rural Nurse Organization; Binghamton University, 2014)
Purpose: An office-based pediatric quality improvement project was implemented to increase the number of well-child health visits and increase the documentation of pediatric quality measures in a Midwest rural clinic. Project Description: The Bright Futures framework provided the structure for the project and a retrospective evaluation was performed six months after the initiation of practice changes, reminder letters, and public service announcements. Chart review was performed with a convenience sample of children ages 0 to 47 months from the database of the organization that supports the family practice clinic and emergency department. The descriptive analysis included change in proportions and percentages and chi-square analyses. Outcomes:  There was an increase the number of well-child visits by 65% in the six month period with a wider range of ages being seen. There was a 40% response rate of visits within two months of the reminder letters. Documentation increased in four out of nine quality measures with two measures remaining at 100%. Validated developmental and behavioral assessment tools were used consistently. A dialogue with the local health department was established to coordinate immunization and well-child visits. Conclusions: The practice changes were found to be sustainable and consistent with quality pediatric care. DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i1.280  Keywords: rural pediatric, office-based, quality improvement